Iron deficiency anemia and glucose metabolism - Soliman, Ashraf T; De Sanctis, Vincenzo; Yassin, Mohamed; Soliman, Nada (Acta Biomedica Atenei Parmensis, 2017)
Iron deficiency anemia (IDA) is a global public health problem affecting both developing and developed countries with major consequences for human health as well as social and economic development. It occurs at all stages of the life cycle, but is more prevalent in pregnant women and young children. IDA appears to be more common in diabetic patients compared to non-diabetic population. Iron deficiency (ID) and IDA can impair glucose homeostasis in animals and human and may negatively affect glycemic control and predispose to more complications in diabetic patients. On the other hand diabetes and its complications are associated with anemia and its correction improves diabetes control and may prevent or delay the occurrence of complications. Physicians treating this form of anemia should be aware of its negative effect on glycemic control in normal and diabetic patients (both type 1 and type 2). They should prevent ID and treat early all those with IDA.This brief review aims to enlighten the different effects of IDA on glucose metabolism in normal and diabetic patients.